Simultaneous seasonal dry/wet signals in eastern and central Asia since the Last Glacial Maximum - S. Peng; Y. Li; Z. Zhang; M. Gao; X. Chen; J. Duan; Y. Xue (Climate of the Past, 2024)
The East Asian monsoon region with the summer precipitation regime and the Mediterranean climate region with the winter precipitation regime show opposite dry/wet changes since the Last Glacial Maximum (LGM). Therefore, different precipitation regimes bring about the opposing changes in dry/wet states between eastern and central Asia (EA and CA). Based on a comprehensive study of modern observational datasets, ensemble simulations of eight climate models from the Paleoclimate Modeling Intercomparison Project phase 3 (PMIP3), and a compilation of 42 proxy records from EA and CA, here we assess the relationship of seasonal precipitation signals involving rain and heat periods and the difference and linkage in dry/wet states from EA and CA. At short-term timescales, empirical orthogonal function (EOF) analysis results of mean annual precipitation show the spatial diversity of overall precipitation patterns in EA and CA. However, EOF results of summer and winter precipitation indicate a similarity between EA and the east of CA, suggesting that seasonal signals of precipitation affected by the Asian monsoon, westerlies, ENSO, the North Atlantic Oscillation (NAO), and the Pacific Decadal Oscillation (PDO) are the primary factors causing the linkage in dry/wet states. At long-term timescales, reconstructed dry/wet states from proxy records since the LGM reveal a parallel evolution in EA and the east of CA as well. A visual inspection from PMIP3 multi-model simulations in summer and winter shows that the insolation in different seasons controls the intensity of westerlies and summer monsoon and further influences the summer and winter precipitation in EA and CA since the LGM. Overall, we suggest, in addition to the traditional difference caused by different precipitation regimes, that dry/wet states in EA and CA universally have inter-regional connections affected by seasonal signals of precipitation at multiple timescales.